2011
DOI: 10.1038/hr.2011.2
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure components and risk for chronic kidney disease in middle-aged Japanese men: The Kansai Healthcare Study

Abstract: It is unclear which blood pressure (BP) components (that is, systolic BP (SBP), diastolic BP (DBP), pulse pressure (PP) and mean arterial pressure (MAP)) are superior predictors of chronic kidney disease (CKD). Furthermore it is unclear whether the combination of SBP+DBP or PP+MAP is superior to any of these four individual BP components in predicting CKD. We enrolled 9928 Japanese men aged 40-55 years who had a normal estimated glomerular filtration rate (eGFR), no proteinuria and no history of cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
2
7
2
Order By: Relevance
“…eGFR was estimated by the 3-variable Japanese equation, defined as follows: eGFR (ml/min/1.73 m 2 ) = 194 × serum creatinine -1.094 × age -0.287 [19]. After an approximate 5-min rest in a quiet room, systolic and diastolic blood pressures were measured in a sitting position with an automatic sphygmomanometer (BP-203RV; Omron Colin, Tokyo, Japan and Udex-super; ELK Corp., Osaka, Japan) [20]. Body mass index (BMI) was calculated as weight in kilograms divided by the square of the height in meters.…”
Section: Methodsmentioning
confidence: 99%
“…eGFR was estimated by the 3-variable Japanese equation, defined as follows: eGFR (ml/min/1.73 m 2 ) = 194 × serum creatinine -1.094 × age -0.287 [19]. After an approximate 5-min rest in a quiet room, systolic and diastolic blood pressures were measured in a sitting position with an automatic sphygmomanometer (BP-203RV; Omron Colin, Tokyo, Japan and Udex-super; ELK Corp., Osaka, Japan) [20]. Body mass index (BMI) was calculated as weight in kilograms divided by the square of the height in meters.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertension has consistently been shown to be an important risk factor for CKD in Western populations [7,8,13,33]. While majority of the studies involving Asian populations [19,34-36] have reported an association between hypertension and CKD, few studies involving Asian Chinese in the US [16], a large cohort of adults in Japan [21] and Korea [22] have documented no significant association of hypertension with CKD. Although hypertension has been shown to be an important risk factor for ESRD in the US general population, ethnic differences have been reported in the association between hypertension and ESRD with blacks having a 4–5 fold increased risk of hypertensive ESRD compared to whites [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…While studies involving Western populations have shown a consistent positive association between systolic BP and CKD, the pattern of association of systolic BP with CKD has not been consistent in Asian populations. Systolic BP was shown to be strong predictor of ESRD in a large cohort of Chinese adults who participated in the China National Hypertension Survey Epidemiology Follow-up Study (CHEFS) [44] and in a large cohort of middle-aged Japanese men who participated in the Kansai Healthcare Study in Japan [19]. However, similar to our findings in Chinese and Indians, three cross-sectional studies involving Chinese [20], and Japanese [21,47] adults reported no significant association between systolic BP and CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC count was measured by the flow cytometry method. After resting approximately 5 min in a quiet room, systolic and diastolic blood pressures were measured in a sitting position with an automatic sphygmomanometer (BP-203RV; Omron Colin, Tokyo, Japan; and Udex-super; ELK Corp., Osaka, Japan) [17]. Body mass index (BMI) was calculated as the weight in kilograms divided by the square of the height in meters.…”
Section: Methodsmentioning
confidence: 99%